Photodegradation of sulfathiazole under simulated sunlight: Kinetics, photo-induced structural rearrangement, and antimicrobial activities of photoproducts - Niu, X.; Glady-Croué, J.; Croue, Jean-Philippe (IWA Publishing, 2017)
© 2017 Elsevier Ltd Photolysis is a core natural process impacting the fate of some sulfonamide antibiotics in sunlit waters. In this study, sunlight-induced phototransformation of sulfathiazole was investigated. A photolytic quantum yield of 0.079 was obtained in buffered water (pH = 8.0). Different natural organic matter isolates inhibited the photolysis of sulfathiazole by light screening effect. A kinetic model was developed to predict the photodegradation rate of sulfathiazole using the light screening correction factor of the water matrix in the wavelength range of 300–350 nm. An isomeric photoproduct of sulfathiazole with a longer retention time was observed on liquid chromatography. Based on its MS/MS spectra and absorption characteristics, the isomer was postulated as 2-imino-3-(p-aminobenzenesulfinyl-oxy)-thiazole. A reaction mechanism for the photo-cleavage and photo-induced structural rearrangement was proposed. The formation mechanism of the isomer was supported by photochemical experiments spiking synthetic 2-aminothiazole; while the formation kinetics were treated with a partly-diffusion-controlled model. The three identified products showed significantly enhanced photo-stability. Antimicrobial assay of irradiated sulfathiazole solutions with Escherichia coli indicated little antimicrobial potency ascribed to photoproducts. This study demonstrates the efficacy of sunlight in rapidly degrading sulfathiazole at a predictable rate, leading to photoproducts of low antimicrobial potency. The mass spectrometry and mechanistic work described here are new insights into the photochemistry of sulfonamides.